ANALISIS VARIABEL– VARIABEL YANG MEMPENGARUHI KINERJA KARYAWAN PADA PERUSAHAAN UMUM PERHUTANI KESATUAN PEMANGKUAN HUTAN SARADAN KABUPATEN MADIUN - M.SI, Dra. Aslichah; Ristyanti, Zheny (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2016)
Performance is an emotional statement in a positive or pleasant as a result of the appreciation of the work and work experience. People will have a level of satisfaction varies according to the value system they act on him, the more aspects of the work in accordance with individual wishes, it will be the higher the perceived level of satisfaction and vice versa. A person's performance is determined by many factors, among others, work discipline factor, high motivation, and a good working environment. The purpose of this study is to; 1) to determine the effect of variable discipline, motivation and work environment on the performance of employees of public companies Perhutani Forest Management Unit Saradan partially. 2) to determine the effect of variable discipline, motivation and work environment on employee performance general company Perhutani Forest Management Unit Saradan simultaneously. 3) to determine which variables are the dominant influence on the general performance of the company's employees Saradan Perhutani Forest Management Unit. A study population of 389 employees and a sample of 80 employees. The sampling technique used was probability sampling. The test to instrument testis is valid and realibilas testis. Hipotesis test us F test, t test and to data analysis, that us regresi berganda testis metod. So important variable is motivation variable. The results of this study recommend that the performance can be improved by taking into account discipline in every job, employee motivation, improve the work environment less comfortable and create a conducive working conditions